In search of a circular supply chain archetype – A content-analysis based literature review - Batista, Luciano; Bourlakis, Michael; Smart, Palie; Maull, Roger (Taylor and Francis, 2018)
This paper addresses questions of how extant research discourses concerning the sustainability of supply chains contribute to understanding about circularity in supply chain configurations that support restorative and regenerative processes, as espoused by the Circular Economy ideal. In response to these questions, we develop a content-based literature analysis to progress theoretical body of knowledge and conceptualise the notion of a circular supply chain. We derive an archetypal form from four antecedent sustainable supply chain narratives - ‘reverse logistics’, ‘green supply chains’, ‘sustainable supply chain management’ and ‘closed-loop supply chains’. This paper offers five propositions about what the circular supply chain archetype represents in terms of its scope, focus and impact. Novel insights lead to a definition of circular supply chain and a more coherent foundation for future inquiry and practice.
Keywords: Circular supply chain; Circular Economy; sustainability perspectives of supply chains; restorative processes